The Effect Of The Random Entry Strategy On Decision-Making Of Fifth-Grade Elementary School Students In The Subject Of Science (Journal of the College of Basic Education, 2024)
The research aims to investigate the impact of the random entry strategy on decision-making among fifth-grade elementary school students in the subject of science. To verify the research objective, the following null hypothesis was formulated: There is no statistically significant difference at a significance level of 0.05 between the average scores of students in the experimental group, who will study using the random entry strategy, and the average scores of students in the control group, who will study using the conventional method on the decision-making scale. The current research community consists of (640) male elementary school students in the fifth grade in Anbar Governorate / Ameriyat Al-Fallujah district The research employed a partial control experimental design for the two experimental and control groups with a two-dimensional test for achievement and a decision-making scale. The research sample consisted of fifth-grade students at Dalouk Al-Shams Elementary School for Boys, a government school under the Anbar Directorate of Education in Ameriyat Al-Sumood. The sample was purposefully selected, comprising 61 students distributed across two classes (A and B). The simple random assignment was used to select Class A as the experimental group, consisting of 30 students, and Class B as the control group, consisting of 31 students. After excluding one failing student from Class B, the number of students in the experimental group became 30, and the number in the control group became 30. A tool to measure decision-making was prepared, consisting of 20 items for the purpose of the post-test. The respondents had two gradual alternatives to answer the items (Yes, No) suitable for the age group. The tool's validity was verified by presenting it to a group of specialists and arbitrators, and a statistical analysis was performed on the scale items (relationship between item score and total scale score, item discrimination). The scale's reliability was calculated using Cronbach's alpha.After completing the experiment, a test for the decision-making scale was conducted on the research sample (experimental and control groups), and the data (research results) were statistically analyzed using the SPSS statistical package. The results showed the superiority of students in the experimental group, who studied using the random entry strategy, over students in the control group, who studied using the conventional method on the decision-making scale. This difference was statistically significant with a large effect size. In light of the research results, the researcher recommends using the random entry strategy in teaching as an alternative to the conventional method and suggests several recommendations